2006
DOI: 10.1073/pnas.0508697103
|View full text |Cite
|
Sign up to set email alerts
|

The Avellino 3780-yr-B.P. catastrophe as a worst-case scenario for a future eruption at Vesuvius

Abstract: A volcanic catastrophe even more devastating than the famous anno Domini 79 Pompeii eruption occurred during the Old Bronze Age at Vesuvius. The 3780-yr-B.P. Avellino plinian eruption produced an early violent pumice fallout and a late pyroclastic surge sequence that covered the volcano surroundings as far as 25 km away, burying land and villages. Here we present the reconstruction of this prehistoric catastrophe and its impact on the Bronze Age culture in Campania, drawn from an interdisciplinary volcanologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 26 publications
2
61
1
Order By: Relevance
“…Although the loss of life and property was less extensive in the Bronze Age eruption than in the eruption of AD 79, owing to the sparser settlements, researchers recently discovered evidence of a massive exodus in the form of a huge number of human and animal footprints, pressed into the ash bed and all leading away from the volcano (Mastrolorenzo et al 2006).…”
mentioning
confidence: 99%
“…Although the loss of life and property was less extensive in the Bronze Age eruption than in the eruption of AD 79, owing to the sparser settlements, researchers recently discovered evidence of a massive exodus in the form of a huge number of human and animal footprints, pressed into the ash bed and all leading away from the volcano (Mastrolorenzo et al 2006).…”
mentioning
confidence: 99%
“…As recent volcanological and archaeoanthropological studies have revealed, an earlier, Bronze Age eruption (around 3780 BC) covered the surrounding area as far as 25 km away, burying land and villages, causing a global climatic disturbance and the abandonment of the entire area for centuries. The loss of life and property was less extensive in the Bronze Age cataclysm than in the eruption of AD 79, but researchers recently discovered evidence of a mass exodus: a huge number of human and animal footprints pressed into the ash bed and all leading away from the volcano (Mastrolorenzo, Petrone, Pappalardo, & Sheridan, 2006 ).…”
Section: Decisions From Experience: a Key To Otherwise Puzzling Humanmentioning
confidence: 99%
“…In fact, the periphery of Mount Vesuvius, which includes a signifi cant chunk of the Naples metropolitan area, is among the most populated of any active volcano (Bruni, 2003 ). According to simulations by Mastrolorenzo et al ( 2006 ), an eruption comparable in magnitude to the Bronze Age eruption would cause total devastation and mortality within a radius of at least 12 km (7½ miles). In addition, great quantities of fi ne ash in more distant zones might cause severe respiratory-tract injuries and fatalities due to acute asphyxia.…”
Section: Decisions From Experience: a Key To Otherwise Puzzling Humanmentioning
confidence: 99%
“…The vulnerability of contemporary Europe, for instance, to extreme events such as a major volcanic eruption are therefore not 'matters of fact' but 'matters of concerns' (Stewart and Lewis 2017). What archaeology can add is immediacy and intimacy to specific volcanic hazard forecast scenarios (e.g., Mastrolorenzo et al 2006;Schmidt et al 2011;Sonnek et al 2017) by focusing on both the vulnerability and the resilience of past communities. People relate readily to the past of the places they live, and indeed draw much of their identity from historical and archaeological narratives (Sommer 2000).…”
Section: Has Noted Thatmentioning
confidence: 99%